The Effect of Think Pair Share Teaching Model to The Reading Comprehension of Seventh Grade Students of SMP Negeri 12 Pematang Siantar in a Descriptive Text - Hutahaean, Rossa Ito; Siahaan, Sanggam (Universitas Pahlawan Tuanku Tambusai, 2024)
This study is about Language is a tool to communicate messages. Language one of the most important thing to communicate because with language we as a human can know the purpose of what people said. In Indonesian, English used as the second language. In order to use a language well, leaners should learn and master the rules of the language in order to know how to speak in the language correctly. Think Pair Share is a collaborative learning strategy where students work together to solve a problem or answer a question about assigned reading. The research will be conducted by using Quantitative. Quantitative research method can be interpreted as the research method that has a certain sample. According to Sugiyono (2012) quantitative research is the research which aims to determine the relationship between two or more variables. This research will use an experimental design to be aware of threasts to both of internal and external validity and consider these factors in the study. There is a pre-test and post-test to find out what ever the use of think pair share teaching model in a descriptive text. This research will be carried out at the SMP Negeri 12 Pematangsiantar at seventh grade, which is located at Jl. Sibolga ,No 25 Pematangsiantar, Sumatera Utara. This research will be carried out in the 2024/2025 academic year. The population of this research will be all the seventh grade of SMP Negeri 12 Pematangsiantar. The population in this study is all students seventh grade of SMP Negeri 12 Pematangsiantar for the academic year 2024/2025, which consists of 9 classes. The findings indicated that the Think Pair Share teaching model was more effective in improving students' understanding of descriptive texts compared to the question-answer model.